Land access in the development of horticultural crops in east Africa: a case study of passion fruit in Burundi, Kenya, and Rwanda - Mpozi, B.B.; Mizero, M.; Egesa, A.O.; Nguezet, P.M.D.; Vanlauwe, Bernard; Ndimanya, P.; Lebailly, Philippe (MDPI, 2020)
Rapid population growth in fertile agricultural lands of East Africa creates land scarcity, which has become a major hindrance to land access for the introduction of new horticultural crops. But their introduction in these areas is increasing, because of their high market price, which improves farmers’ income. As such, this research evaluated land access dynamics (availability, acquisition, and use changes) on the introduction of passion fruits in East Africa. The study used purposeful sampling to collect information from 171 passion fruit farmers from Burundi (60), Kenya (51), and Rwanda (60) through interviews during field surveys. Among the respondents from all three countries, inheritance and land purchase were the predominant modes of land access (>50% and >21%, respectively). Furthermore, the substitution of other crops by passion fruits was high (>60%) among Kenyan and Rwandan farmers, but low (18%) among Burundian farmers. Our findings indicate that land access influences the patterns of adoption of new crops, since, when limited in supply, it may require the acquisition of new land space, abandonment of other crops, or opting for mixed farming. As such, land access should be a consideration in the promotion of new crops for sustainable agricultural ventures.